2016
DOI: 10.1007/s13671-016-0136-7
|View full text |Cite
|
Sign up to set email alerts
|

Two Decades of Teledermatology: Current Status and Integration in National Healthcare Systems

Abstract: Teledermatology, originating in 1995, has been one of the first telemedicine services to see the light of day. Two decades of teledermatology research is summarized in this review. A literature search was conducted in PubMed. Search terms included “teledermatology,” “teledermoscopy,” “tele wound care,” “telederm*,” “(dermatology OR dermoscopy OR wound care OR skin) AND (telemedicine OR ehealth or mhealth OR telecare OR teledermatology OR teledermoscopy).” Inclusion criteria were (i) Dutch or English written pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
143
0
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(160 citation statements)
references
References 39 publications
2
143
0
15
Order By: Relevance
“…On the one hand, this result may lead to further studies in the general population to assess the performance of the procedures in a primary care setting. On the other hand, this review emphasizes that the publication of data related to up-to-date technologies is a challenge in teledermatology [20,66]; it is notable that up to 70% of the photographs were of poor quality in a study performed in 2007 [51], whereas all photographs were interpretable in 2016 [50].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the one hand, this result may lead to further studies in the general population to assess the performance of the procedures in a primary care setting. On the other hand, this review emphasizes that the publication of data related to up-to-date technologies is a challenge in teledermatology [20,66]; it is notable that up to 70% of the photographs were of poor quality in a study performed in 2007 [51], whereas all photographs were interpretable in 2016 [50].…”
Section: Discussionmentioning
confidence: 99%
“…Patients reported that one limitation of the applications was the difficulty of not having any human contact [20]. For both procedures, a limitation was the loss of the face-to-face patientphysician relationship, which may be critical since a melanoma is diagnosed early, at a severe stage, or in the ageing population [35,40,49,73].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations